Benefit of Treatment Individualization in Patients with Chronic Hepatitis C Receiving Peginterferon Alfa-2a and Ribavirin in a Large Noninterventional Cohort Study. - Wolf Peter Hofmann (PLoS ONE, 2015)
Individualization of treatment with peginterferon alfa and ribavirin in patients with chronic hepatitis C showed benefit in controlled trials and was implemented in treatment guidelines to increase response rates and to reduce side effects and costs. However, it is unknown whether individualization was adopted in routine daily practice and whether it translated into improved outcomes.From a large noninterventional cohort study, clinical and virologic response data of 10,262 HCV patients who received peginterferon alfa-2a and ribavirin between 2003-2007 and 2008-2011 were analyzed. To account for treatment individualization, a matched-pair analysis (2,997 matched pairs) was performed. Variation in treatment duration and dosing of ribavirin were analyzed as indicators for individualization.Sustained virological response (SVR) rates were similar between 2003-2007 and 2008-2011 (62.0% vs. 63.7%). Patients with comorbidities were more abundant in the later period, (44.3% vs. 57.1%). The subsequent matched-pair analysis demonstrated higher SVR rates in the 2008-2011 period (64.3%) than in the 2003-2007 period (61.2%, p=0.008). More patients received abbreviated or extended treatment regimens in the later than the earlier period as an indicator of treatment individualization. To the same end, ribavirin doses were higher in the later period (12.6 versus 11.6 mg/kg/day). Factors independently associated with SVR included HCV genotype, low baseline viral load, younger age, route of infection, absence of concomitant diseases, lower APRI score, normal gamma-GT, higher ribavirin doses, no substitution for drug abuse, treatment duration, and treatment in the 2008-2011 period.Treatment individualization with peginterferon alfa and ribavirin was implemented in daily routine between 2003-2007 and 2008-2011, SVR rates improved in the same period. These findings may be most relevant in resource-limited settings.